2015
DOI: 10.1002/term.2099
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional co-culture of human hepatocytes and mesenchymal stem cells: improved functionality in long-term bioreactor cultures

Abstract: The development of human cell models that can efficiently restore hepatic functionality and cope with the reproducibility and scalability required for preclinical development poses a significant effort in tissue engineering and biotechnology. Primary cultures of human hepatocytes (HHs), the preferred model for in vitro toxicity testing, dedifferentiate and have short-term viability in two-dimensional (2D) cultures. In this study, hepatocytes isolated from human liver tissue were co-cultured with human bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 44 publications
1
60
0
3
Order By: Relevance
“…Previous studies demonstrated that the co‐culture of hepatocytes with other cell types such as sinusoidal cells, MSCs, and fibroblasts improved maintenance of liver cell function. 3D matrices composed of natural collagen or synthetic biomaterials have been used to culture hepatocytes .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the co‐culture of hepatocytes with other cell types such as sinusoidal cells, MSCs, and fibroblasts improved maintenance of liver cell function. 3D matrices composed of natural collagen or synthetic biomaterials have been used to culture hepatocytes .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cells in this study retained their RNA expression levels of various phase I (CYP1A2, CYP2C9, and CYP3A4) and phase II enzymes (GSTA1 and UGT2B7). Coculturing PHH in stirred bioreactors with an outer layer of bone marrow mesenchymal stem cells have been shown to further increase the expression of these cytochrome P450s (CYPs), whereas functional parameters (urea and albumin) were not affected . While these results are promising regarding the molecular phenotypes and activities of the cultured cells, bioreactors require large numbers of cells and form spheroids of heterogeneous sizes, which complicates analyses and is incompatible with high‐throughput testing of different conditions.…”
Section: D Culture Paradigms For Phhmentioning
confidence: 99%
“…Coculture with mesenchymal stem cells (MSCs) provides primary human hepatocytes with direct structural and paracrine trophic support, resulting in improved viability and function . Another strategy that may improve hepatocyte functionality is 3D culture . Aggregation into organoid‐like structures has been tested in primary hepatocytes and stem cell‐derived HLCs with and without MSC coculture, yielding promising results both in terms of functionality and engraftment .…”
Section: Use Of Primary Hepatocytes Versus Stem Cellsmentioning
confidence: 99%